HOW DO NARCISSISTIC LEADERS RELATE TO EMPLOYEE ORGANIZATION CITIZEN BEHAVIOR (LEADER MEMBER EXCHANGE AS A MEDIATION VARIABLE) - Anggia Boantua Siahaan; Kabul Wahyu Utomo (Dinasti Publisher, 2022)
This research aims to see the Relationship of Narcissistic Leadership with Organizational Citizen Behavior Mediated by Leader Member Exchange. This study uses Organizational Citizen Behavior as a dependent variable and Narcissistic Leadership as an independent variable. This study used quantitative research methods with sampling techniques in the form of purposive sampling which were distributed to office workers in the Central Jakarta area with an age range in the Millennial generation, namely 20 years to 40 years. The number of populations in this study is unknown, so the sampling used the Lame show technique with a total sample of 100 respondents. The results of the linear regression in this study showed that the proposed hypothesis corresponded to the research carried out. Where the results of the study showed a significant relationship between narcissistic leadership and employee organizational citizen behavior. The results also showed that leader member exchange can mediate the relationship between narcissistic leadership variables and employee organizational citizen behavior.